(untitled) (Research, Society and Development, 2021)
Enteroparasitosis is a serious public health problem due to the high number of people affected and the organic changes that can be caused. They affect individuals of all age groups, but mainly school children. Thereby, the objective is to build a bibliographic review on enteroparasitism in children in Northeast Brazil between the years 2015 to 2020. The research is descriptive and qualitative, whose material came from the results found in the databases of the Virtual Health Library and Google Scholar. 160 studies were found. After applying the inclusion and exclusion criteria, 37 articles were analyzed, 1 from Alagoas, 1 from Sergipe, 1 from Rio Grande do Norte, 2 from Pernambuco, 4 from Bahia, 5 from Piauí, 7 from Ceará, 8 from Paraíba and 8 from Maranhão. It was possible to verify that the prevalence of enteroparasitosis in children is still a problem in Northeast Brazil and remains high, indicating difficulties in accessing health education and in controlling infections. Therefore, it is evident the need for measures that reduce or even eliminate infection processes, such as prophylactic actions and educational activities in health.